PROFESSIONAL EXAMINATIONS–ACCOUNTING PRACTICE. - Beckert, Ralph F.; Chamberlain, John H. (The Accounting Review, 1965)
Abstract This article presents problems which were prepared by the Board of Examiners of the American Institute of Certified Public Accountants (C.P.A) and were presented as the first half of the C.P.A. examination in accounting practice which held on November 4, 1964.